Unraveling the rise and fall of quick commerce in Indonesia: insights from industry experts - Anisa, Mutia; Purwanegara, Mustika Sufiati (Entrepreneurship Bisnis Manajemen Akuntansi (E-BISMA), 2025)
The quick commerce business model experienced significant popularity in Jakarta and its surrounding areas in 2022, offering consumers enhanced convenience through fast delivery services. However, this success was short-lived, with several quick commerce platforms collapsing just months after their launch. This study explores the factors behind the rapid rise and subsequent decline of quick commerce in Indonesia. Using a qualitative approach, in-depth interviews were conducted with two industry experts specializing in e-grocery and digital economics. The interviews were analyzed with NVivo software to identify key themes and patterns. The findings show that quick commerce grew due to pandemic-driven changes in consumer behavior, global trends, and a novel customer experience offering convenient delivery solutions. However, its decline was driven by high costs, low profitability, and difficulties in managing products like fresh produce, which had quality issues and short shelf lives. It also faced strong competition from minimarkets and supermarkets moving online, using existing infrastructure to provide similar services at lower costs. Shifting consumer habits after the pandemic and inconsistent demand further weakened the business model's sustainability. These insights provide theoretical and practical contributions, offering strategies for addressing challenges in emerging business models and ensuring their sustainability in dynamic retail environments.